The Power of Quiet: Re-making Affective Amateur and Professional Textiles Agencies. (2nd January 2016) - Hackney, Fiona; Maughan, Hannah; Desmarais, Sarah
Abstract: This article advocates an enlarged understanding of the benefits of manual creativity for critical thinking and affective making, which blurs the boundaries, or at least works in the spaces between or beyond differential definitions of amateur and professional craft practices and identities. It presents findings from the Arts and Humanities Research Council (AHRC) funded project: Co-Producing CARE: Community Asset-based Research & Enterprise (https://cocreatingcare.wordpress.com ). CARE worked with community groups (composed of amateur and professional textile makers) in a variety of amateur contexts: the kitchen table, the community cafe, the library, for instance, to explore how critical creative making might serve as a means to co-produce community agency, assets and abilities. The research proposes that through "acts of small citizenship" creative making can be powerfully, if quietly, activist. Unlike more familiar crafts activism, such "acts" are not limited to overtly political and public manifestations of social action, but rather concern the micro-politics of the individual, the grass roots community and the social everyday. The culturally marginal, yet accessible nature of amateur crafts becomes a source of strength and potential as we explore its active, dissenting and paradoxically discontented aspects alongside more frequently articulated dimensions of acceptance, consensus and satisfaction. Informed by work on cooperation, DIY citizenship, critical making, and theories of embodied and enacted knowledge, the authors interpret findings from selected CARE-related case studies to explicate various ways in which "making" can make a difference by: providing a safe space for disagreement, reflection, resolution, collaboration, active listening, questioning and critical thinking, and offer quiet, tenacious and life-enhancing forms of resistance and revision to hegemonic versions of culture and subjectivity.